Evaluating high growth entrepreneurs' knowledge of the South African Small Medium and Micro Enterprise policy framework and impact of such knowledge on business performance - Van Vuuren, Jurie Jansen (University of Pretoria, 2022)
Thesis (PhD (Entrepreneurship))--University of Pretoria, 2021.